Occipital lobe and posterior cingulate perfusion in the prediction of dementia with Lewy body pathology in a clinical sample. Issue 12 (December 2017) - Prosser, Angus M.J.; Tossici-Bolt, Livia; Kipps, Christopher M.
Abstract : Objective: The aim of this study was to investigate the diagnostic value of occipital lobe and posterior cingulate perfusion in predicting dopamine transporter imaging outcome using a quantitative measure of analysis. Patients and methods: In total, 99 patients with cognitive complaints who had undergone both technetium-99m-hexamethylpropyleneamine oxime single-photon emission computed tomography ( 99m Tc-HMPAO SPECT) and 123 I ioflupane ( 123 I-FP-CIT also called DaTSCAN) imaging in a dementia diagnostic center were analyzed. Measures of perfusion were calculated from HMPAO SPECT images for the medial and lateral occipital lobe, the posterior cingulate cortex, precuneus and cuneus regions of interest using statistical parametric mapping 8. DaTSCAN images were quantified and specific binding ratios were calculated independent from HMPAO SPECT results. Statistical parametric mapping and tests of associations between perfusion and 123 I-FP-CIT imaging were completed. Results: Regions of interest on HMPAO yielded poor predictive values when used independently to predict 123 I-FP-CIT status; however, the combination of normal posterior cingulate perfusion with medial and lateral occipital hypoperfusion was associated significantly with 123 I-FP-CIT status, χ 2 (1, N= 99)=9.72, P= 0.002. This combination also yielded a high positive likelihood ratio and specificity (11.1, 98%). Sensitivity was, however, low (22%). No significant perfusion differences were found when abnormal and normal 123 I-FP-CIT groups were compared directly using voxel-based morphometry ( P <0.05, family-wise error). Conclusion: The combination of medial and lateral occipital hypoperfusion with preserved posterior cingulate gyrus perfusion is highly specific for individuals with a positive 123 I-FP-CIT scan in a clinical sample where diagnostic doubt exists. This regional combination, however, lacks sensitivity; therefore, absence of the sign cannot be used to rule out dementia with Lewy bodies. A positive finding provides strong evidence to rule in dementia with Lewy bodies.